Social and Health Status of Elderly Population in Far-Western Region - Bhatta, R (2016)
Background: In Nepal, the older population is increasing both in terms of absolute numbers and as a proportion of the total population, i.e. there were 1.6 million elderly inhabitants, which constitute 7.46% of the total population in 2001, which is estimated to be double by 2017. This population is also regarded to be vulnerable as they suffer from the cumulative effects of a lifetime of deprivation, poor health and nutrition, low social status, discrimination and restriction on mobility, lack of means to fulfill their basic needs such as food, clothes, shelter, health care, love and affection. This study is thus designed to assess their social and health situation. Methods: This is a descriptive/cross-sectional study and includes both qualitative as well as quantitative data. Three districts of far-western development region were selected randomly having one each from terai, hilly and mountainous area; Kanchanpur, Doti and Darchula respectively. From each district one VDC was randomly selected and out of the total ward of the VDC, one ward was randomly selected from where the all the population above the age of 60 years were taken for the study. A total 325 subjects were interviewed using this pre-tested questionnaire by the health personnel who were trained by the investigators. The collected data was tabulated and analyzed using the statistical package SPSS, Version 11.5 for Windows. Findings were described using proportions and percentage. Results: The study showed that only 45% of the respondents were satisfied with the status of their living home. 44% of the respondents told that they don’t had any sources of income. Majority of the elderly peoples above 70 years told that they get the elderly allowance that is being provided by the government, but they are not getting it regularly. Only about 63% of the respondents were satisfied with their relation. The findings showed that only about 48% of the respondents were found to be satisfied with the daily food that they take. On the major health problems of the respondents that were identified among the respondents were eye problem (among 93%), dental problems (among 80%), digestive problem (54%), respiratory problems (among 45%), skeletal and muscular problems (among 46%), urinary problems (among 28%) and cardiovascular problem (among 19%). Although the existence of the problem was found to be at higher rate but it was found that only about 17% of respondents were having regular health checkup, which is considerably low. Study finding showed that 11% of the respondents were just confined to the bed due to the severity of problem. About 9% of them expressed that they were unable for washing, bathing and changing their cloths. Similarly 19% of the respondents expressed that they are unable to perform their usual activities and about 18% of the respondents expressed that they have extreme pain and discomfort. Study results showed that about 31% of the respondents were extremely anxious and depressed. Conclusions: Elderly peoples have considerable health and social problems. In developing county like Nepal, it is necessary to develop senior citizen welfare program in such a way so that they can maintain their social and health status and develop the feeling of “senior” not “old and absolute”.